EFFICIENCY AND EFFECTIVENESS OF E-RETRIBUTION INNOVATION IN SAMPANGAN MARKET AND JERAKAH MARKET - Kunto Wibisono; Budi Puspo Priyadi; Hardi Warsono (DIA: Jurnal Administrasi Publik, 2022)
Sampangan Market and Jerakah Market are two markets in Semarang City that have implemented e-retribution since 2018. The implementation of market e-retribution that has been implemented in Semarang City so far has encountered several obstacles, such as technical problems in the payment or withdrawal system, human resources from the management bank is still lacking, as well as people's market traders who have not been able to use and implement e-retribution optimally. The purpose of this study was to assess the effectiveness and efficiency of the implementation of e-retribution in Sampangan Market and Jerakah Market. This research was quantitative descriptive. The data in this study were primary data obtained through the Regional Coordinator of the Semarang City Government Market Service and research journals. Data processing used Microsoft Excel. The data analysis technique was carried out using the calculation of Cost Of Collection Efficiency Ratio (CCER) and Change Performance Index (CPI). The results showed that the CCER values ​​in the Sampangan Market and Jerakah Market were 50.64% and 40.64% respectively in 2018, and 28.59% and 37.12% in 2020. The CPI value in the Sampangan Market and Pasar Jerakah Jerakah was 91.30% and 90.35% respectively in 2018, and 90.40% and 92.32% in 2020. This study concluded that the implementation of e-retribution in Sampangan Market and Jerakah Market is efficient and effective.